Measurement of the maximum oxygen uptake VO2max: VO2peak is no longer acceptable - Poole, D.; Jones, A. (Journal of Applied Physiology, 2017)
The maximum rate of O2 uptake (i.e., VO2max), as measured during large muscle mass exercise such as cycling or running, is widely considered to be the gold standard measurement of integrated cardiopulmonary-muscle oxidative function. The development of rapid-response gas analyzers, enabling measurement of breath-by-breath pulmonary gas exchange, has facilitated replacement of the discontinuous progressive maximal exercise test (that produced an unambiguous VO2-work rate plateau definitive for V2max) with the rapidly incremented or ramp testing protocol. Although this is more suitable for clinical and experimental investigations and enables measurement of the gas exchange threshold, exercise efficiency, and V2 kinetics, a VO2-work rate plateau is not an obligatory outcome. This shortcoming has led to investigators resorting to so-called secondary criteria such as respiratory exchange ratio, maximal heart rate, and/or maximal blood lactate concentration, the acceptable values of which may be selected arbitrarily and result in grossly inaccurate VO2max estimation. Whereas this may not be an overriding concern in young, healthy subjects with experience of performing exercise to volitional exhaustion, exercise test naïve subjects, patient populations, and less motivated subjects may stop exercising before their VO2max is reached. When VO2max is a or the criterion outcome of the investigation, this represents a major experimental design issue. This CORP presents the rationale for incorporation of a second, constant work rate test performed at ~110% of the work rate achieved on the initial ramp test to resolve the classic VO2-work rate plateau that is the unambiguous validation of VO2max. The broad utility of this procedure has been established for children, adults of varying fitness, obese individuals, and patient populations.